Supplementation of Heit-Chrose into Dairy Cow Feed Improves in Vitro Rumen Fermentation - Prayitno, Caribu Hadi (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2015)
The objective of the study was to evaluate the effect of Heit-Chrose (HC) supplementation using in vitro method on ruminal fermentation of dairy cattle. HC is a feed supplement containing allicin, saponin and organic minerals ( Se , Cr and Zn). This research was conducted using completely randomized design, with 6 treatments and 4 replications. The treatments were : 1). C = dairy cattle feed (CP 15.38%, CF 23.38%, TDN 61.26%); 2). HC-0 = C+ organic minerals (0.3 ppm Se + 0.15 ppm Cr + 40 ppm Zinc-lysinat) + 0 ppm of HC; 3). HC-15= C + 15 ppm HC; 4).HC-30 =C+ 30 ppm of HC; 5). HC-45 =C+ 45 ppm of HC; 6). HC-60 =C + 60 ppm of HC. Data obtained were analyzed using analysis of variance of SPSS program. HC supplementation increased the DMD, OMD, VFA, but reduced total gas, methane and protozoa count. HC supplementation greater than 30 ppm did not further improve ruminal fermentation. Supplementation at 30 ppm of HC to dairy cow feed was the appropriate level to improve the efficiency of rumen fermentation.